2017
DOI: 10.11113/jt.v79.11330
|View full text |Cite
|
Sign up to set email alerts
|

A New Design Enhances Hydrogen Production by G. Sulfurreducens Pca Strain in a Single-Chamber Microbial Electrolysis Cell (Mec)

Abstract: Microbial electrolysis cell (MEC) is an innovative and green technology to generate hydrogen from a wide range of renewable energy sources and wastewater. At current stage, the performance of these systems is still far from real-world applications. The most likely limiting factors for successful commercialization of this technology are the large internal resistance, high fabrication and operational costs. The aim of the present study was to enhance hydrogen production, reduce the construction and operational c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In general, the essential components for the construction and operation of an MEC include a power supply with constant DC source typically between 0.2-0.8V, a microbial enriched anode, a catalyzed cathode (e.g., Pt catalyzed cathode) and a well-designed gas collection system. Different architecture exists (Kadier et al 2016b;Kadier et al 2017c) and they are basically optimized for the process/application that the MECs is built on but important parameters considered include anode-cathode distance, flow rates and configuration and presence/absence of a membrane. Recent studies Kadier et al 2017c) have confirmed that a single-chamber MEC is cost-effective and lead to an increase in the coulombic efficiency (CE) of the entire process.…”
Section: Working Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the essential components for the construction and operation of an MEC include a power supply with constant DC source typically between 0.2-0.8V, a microbial enriched anode, a catalyzed cathode (e.g., Pt catalyzed cathode) and a well-designed gas collection system. Different architecture exists (Kadier et al 2016b;Kadier et al 2017c) and they are basically optimized for the process/application that the MECs is built on but important parameters considered include anode-cathode distance, flow rates and configuration and presence/absence of a membrane. Recent studies Kadier et al 2017c) have confirmed that a single-chamber MEC is cost-effective and lead to an increase in the coulombic efficiency (CE) of the entire process.…”
Section: Working Principlesmentioning
confidence: 99%
“…Different architecture exists (Kadier et al 2016b;Kadier et al 2017c) and they are basically optimized for the process/application that the MECs is built on but important parameters considered include anode-cathode distance, flow rates and configuration and presence/absence of a membrane. Recent studies Kadier et al 2017c) have confirmed that a single-chamber MEC is cost-effective and lead to an increase in the coulombic efficiency (CE) of the entire process.…”
Section: Working Principlesmentioning
confidence: 99%
“…It has been reported that single chamber membrane free MEC with graphite brush anode with closer electrode spacing achieved a maximum hydrogen production rate of 3.12 ± 0.02 m 3 H 2 /m 3 reactor/d at an applied voltage of 0.8 V 53 . Use of Geobacter sulfurreducens strain as a medium has improved the performance by minimizing the electrode spacing and internal resistance at 1.1 V 54,55 . The performance of the system was generally determined by changes toward the applied voltage 56 .…”
Section: Various Configuration Of Mecmentioning
confidence: 99%